Pengaruh Manajemen Kasus HIV/AIDS Terhadap Kualitas Hidup Pasien HIV/AIDS - Maria Karolina Selano; Untung Sujianto; Bambang Edi Warsito (Jurnal Keperawatan Notokusumo, 2016)
Background : The implementation of HIV/AIDS?s case management with ineffective quality of service will impact on the the life quality of HIV/AIDS?s patients. The life quality is an important component in evaluating the welfare and the life of ODHA. Objective : This study aims to determine the impact of HIV/AIDS?s case management on the quality of life of HIV/AIDS?s patients. Method : This study used a quasy research method experiment with the pretest-posttest control group design. The population is the HIV/AIDS patients that are undergo a treatment in the Hospital in Sorong City. The researchsamples are 66 respondents, the statistic test that are used are paired t-test, Independent t-test and simple linear regression. Result : The result from 33 respondents of intervention group and 33 control group showed that there are significant difference in the quality of life of HIV/AIDS?s patients before and after receiving training in the intervention group (p value 0.001) with the average increase value of 14.06, while the control group is 1.96. Conclusion : It is concluded that there are a significant impact of HIV/AIDS case toward the life quality of the HIV/AIDS patients. Where every increasing value of case management are capable to increase the life quality of patients as much as 0,259.